BRASSINOSTEROID-SIGNALING KINASE1-1, a positive regulator of brassinosteroid signalling, modulates plant architecture and grain size in rice. (8th November 2022) - Tian, Peng; Liu, Jiafan; Yan, Baohui; Zhou, Chunlei; Wang, Haiyang; Shen, Rongxin
Abstract: Brassinosteroids (BRs) are a crucial class of plant hormones that regulate plant growth and development, thus affecting many important agronomic traits in crops. However, there are still significant gaps in our understanding of the BR signalling pathway in rice. In this study, we provide multiple lines of evidence to indicate that BR-SIGNALING KINASE1-1 (OsBSK1-1) likely represents a missing component in the BR signalling pathway in rice. We showed that knockout mutants of OsBSK1-1 are less sensitive to BR and exhibit a pleiotropic phenotype, including lower plant height, less tiller number and shortened grain length, whereas transgenic plants overexpressing a gain-of-function dominant mutant form of OsBSK1-1 (OsBSK1-1 A295V ) are hypersensitive to BR, and exhibit some enhanced BR-responsive phenotypes. We found that OsBSK1-1 physically interacts with the BR receptor BRASSINOSTEROID INSENSITIVE1 (OsBRI1), and GLYCOGEN SYNTHASE KINASE2 (OsGSK2), a downstream component crucial for BR signalling. Moreover, we showed that OsBSK1-1 can be phosphorylated by OsBRI1 and can inhibit OsGSK2-mediated phosphorylation of BRASSINOSTEROID RESISTANT1 (OsBZR1). We further demonstrated that OsBSK1-1 genetically acts downstream of OsBRI1, but upstream of OsGSK2 . Together, our results suggest that OsBSK1-1 may serve as a scaffold protein directly bridging OsBRI1 and OsGSK2 to positively regulate BR signalling, thus affecting plant architecture and grain size in rice. Abstract : A brassinosteroid (BR) signalling regulator, OsBSK1-1, directly bridges the BR receptor OsBRI1 and the BR signalling suppressor OsGSK2, and provides new insights into BR signalling mechanisms that regulate rice plant architecture and grain size.